Dominant Actors and Political Communication related to The New National Capital City in Indonesia (Ibu Kota Negara - IKN) - Wijayanti, Chory Angela; Priyowidodo, Gatut (Penerbit Goodwood, 2025)
Purpose: This study aims to see who the dominant actor or communicator in the IKN. Methodology/approach: This research using the quantitative content analysis research method, and researchers will analyze the four types of engagements Results/findings: The results showed that Muhammad Said Didu through the account @msaid_didu, is at the top for like and retweet interactions. Meanwhile, Ridwan Kamil (@ridwankamil), was ranked 1st and 2nd for reply. Ridwan Kamil also got the highest quote interaction. The topic of moving the IKN involved well-known figures accounts such as Hidayat Nur Wahid and Sudjiwo Tedjo. In addition, accounts that are also involved and get high user engagement are accounts belonging to the media, such as Tempo (@tempodotco), Kompas (@kompascom and @kompasTV), Kumparan (@kumparan), and CNN Indonesia (CNN Indonesia). Conclusions: The study reveals that personal accounts, particularly those of Muhammad Said Didu and Ridwan Kamil, dominate political communication about the National Capital City (IKN) issue on Twitter. Despite having fewer followers than media outlets, these individuals achieved higher engagement through more personal and interactive communication styles. In contrast, media accounts tended to act as one-way information sources, generating less audience interaction. The findings highlight that authenticity and direct engagement are key to influencing public discourse on political issues in the digital era. Limitations: The limitation of this research is that it does not look at the audience to be able to describe the impact of the communication carried out. Contribution: This research is useful for the development of communication science, especially in the area of ??media and political communication.